Low Cost Tunable Bandstop Filter Design of Defected Ground Structure using FR4 Substrate - Ahmad, B. H.; Shairi, N. A.; Saveridass, J. (2013)
Abstract- This paper presents a tunable bandstop filter design using defected ground structure (DGS) where FR4 substrate is used as a low cost solution compared to others substrate such as Teflon and Rogers RT/Duroid. Thus, the performance of the tunable DGS bandstop filter using FR4 substrate is analyzed in this paper. Besides, analytical modeling of the tunable bandstop filter is derived and discussed as well where the tunable element of varactor diodes are used in the design. As result, tuning range in simulation is achieved from center frequency of 0.445 to 1.99GHz while the tuning range of fabricated filteris from 0.495 to 1.88GHz. The range of bandstop attenuation is between 9 to 46 dB for tuning voltage between 0 to 8 V.